MAGNETIZING ROASTING OF IRON LATERITE ORE BY SUB-BITUMINOUS COAL AS REDUCTANT - NURYADI SALEH; PRAMUSANTO PRAMUSANTO (Puslitbang tekMIRA, 2006)
The overburden of Pomalaa’s laterite ore is characterized by its high content of iron with average Fe content of 41.8 % and can be classified as iron cap deposit. As a significant iron ore resource to be used as raw material for iron and steel industry, upgrading of laterite ore is necessary to meet the requirement for iron making. The ore was treated by magnetized roasting technique followed by mag- netic separation to produce high iron content of magnetic concentrate. The ore were dominated by limonite iron minerals and has low magnetic property. However, roasting reduction treatment increased the magnetic properties of the ore due to transformation of magnetite.